Phase evolution, microstructure and thermo-mechanical characteristics of titania bearing spinel-periclase refractories for Rh degasser - Mandal S.; Dileep Kumar C.J.; Adak S.; Kumar D.; Chattopadhyay A.K. (My University, 2025)
RH Degasser refractories experience extreme operating conditions especially those used in lower vessel and snorkel. The major factors that contribute to the degradation are erosion, steel and slag penetration and spalling. The refractories for this application should possess good hot strength to achieve the required erosion resistance along with excellent thermal shock resistance. In addition to this, they are expected to have good corrosion resistance to the slag in Degasser. Direct bonded magnesia-chrome refractory is the standard for this application. Adverse environmental effect of chromium bearing refractories is fuelling the research to develop an alternative. Even though spinel-periclase refractories have the potential to be a replacement, considerable improvement in erosion and spalling resistance is required to make it successful. Having an engineered microstructure with low porosity and very good sintering is a prerequisite to meet the requirements. This paper evaluates the characteristics of an in-situ spinel bonded Spinel-Periclase refractory with titania addition to ascertain its suitability for this challenging application. In contrary to a previous work from our laboratory, which used iron bearing rutile mineral, ultrafine pure titania (Anatase) has been used to ensure uniform distribution, high reactivity and purer matrix which is expected to have high erosion resistance. The grading and phase composition were carefully engineered to obtain the desired microstructure. Optimized chemical composition as well as the particle size distribution to achieve an in-situ spinel content of about 14% and an apparent porosity below 13%. The prepared compositions were evaluated for their sintering, microstructure, cold and hot strength, as well as thermal shock resistance. A potential chrome free spinel-periclase refractory with properties closely matching to that of standard RH Degasser Magnesia-Chrome composition was demonstrated. © 2015 The American Ceramic Society. All rights reserved.